1984
DOI: 10.1002/vnl.730060303
|View full text |Cite
|
Sign up to set email alerts
|

The lubrication mechanism of calcium stearate/paraffin wax systems in PVC compounds

Abstract: The lubrication mechanism in PVC was studied using calcium stearate and paraffin wax lubricants. Based on the results of the differential thermal analyses, percent haze, microscopy, metal release, Brabender fusion, and extrusion studies we have developed a new theory of PVC lubrication based on molecular structure. Lubricants containing polar groups, which preferentially wet the metal surface in the presence of PVC, such as calcium stearate, are excellent metal lubricants. Non‐polar lubricants which do not wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 7 publications
4
34
0
Order By: Relevance
“…Indeed, it has already been shown that calcium stearate can modify the fusion process of PVC. 6 At the steady state of processing, the pressure decreases with increasing the stearates concentration, meaning that the slip amplitude increases with the stearates concentration. Furthermore, the transient time for reaching the steady state increases with the stearates concentration.…”
Section: Evidence Of Slip Phenomenonmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it has already been shown that calcium stearate can modify the fusion process of PVC. 6 At the steady state of processing, the pressure decreases with increasing the stearates concentration, meaning that the slip amplitude increases with the stearates concentration. Furthermore, the transient time for reaching the steady state increases with the stearates concentration.…”
Section: Evidence Of Slip Phenomenonmentioning
confidence: 99%
“…This result means that the addition of stearate at a lower concentration than 0.84 phr does not modify the viscous behaviour of the PVC compound. Calcium stearate is known to be insoluble in PVC, 6 and it can be assumed that zinc stearate is not soluble. Indeed, in the case of solid particles in low volume concentration, the bulk viscosity of the compound can be assumed to be independent of the particle concentration.…”
Section: Evidence Of Slip Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…Hm is more easily emulsified by soap than Hv because it does not form a soap film. However, the soap film does not create on oil film as in the case of Hv, due to deterioration of the oil film by solubilization in the presence of soaps at the interface (Rabinovitch et al 1984). The correlations established between the ability to reduce friction and physicochemical measurements make it possible to identify two processes that intervene close to the formwork: -The emulsification of hydrocarbons (Hm) and esters (Hv) by the soaps formed; and -The transformation of esters into soap (saponification), catalyzed by fatty acids (acidifiers) present in the oil, which are themselves turned into soap (salts of fatty acids).…”
Section: Interfacial Phenomenamentioning
confidence: 99%
“…The correlations established between the ability to reduce friction and physicochemical measurements make it possible to identify two processes that intervene close to the formwork: -The emulsification of hydrocarbons (Hm) and esters (Hv) by the soaps formed; and -The transformation of esters into soap (saponification), catalyzed by fatty acids (acidifiers) present in the oil, which are themselves turned into soap (salts of fatty acids). In the case of Hv, the interface forms two layers (Rabinovitch et al 1984). The ester molecules, owing to their polarity, adsorb preferentially on the metal wall of the formwork by chemical interactions (Jacquet et al 1974).…”
Section: Interfacial Phenomenamentioning
confidence: 99%